International approaches to legal regulation of juvenile justice and juvenile prevention - Pastukh, Igor; Bass, Viktoriya; Bukhtiiarov, Oleksii Anatoliiovych; Maksymenko, Olena (Maracaibo: Universidad del Zulia. Instituto de Estudios Políticos y Derecho Público, 2022)
The article is dedicated to investigation of different approaches in the field of juvenile prevention and juvenile justice. The article examines the features of juvenile justice and juvenile prevention in different countries, in particular, in the United States, Britain, France, the Netherlands, Germany, Italy, Ukraine. The existing models of organizing the activities of the juvenile police, other specialized bodies and institutions for children operating in foreign countries are considered. The issues of organization and implementation of crime prevention among children in different countries of the world have been studied. Special attention is paid to the US experience in the field of juvenile justice and juvenile prevention. In particular, the system of specialized bodies and institutions for children in the United States was studied. International systemic acts on the settlement of juvenile liability are analyzed. The analysis of world models of juvenile justice, in particular, Anglo-Saxon, continental, Scandinavian, is carried out and their peculiarities are singled out. The positive features of each of these models, which can be borrowed, in particular, by Ukraine, have been identified.

Стаття присвячена дослідженню різних підходів у сфері ювенальної превенції та ювенальної юстиції. У статті розглядаються особливості ювенальної юстиції та ювенальної превенції в різних країнах, зокрема, у США, Великій Британії, Франції, Нідерландах, Німеччині, Італії та Україні. Розглянуто існуючі моделі організації діяльності ювенальної поліції, інших спеціалізованих органів та дитячих установ, що діють у різних країнах. Досліджено питання організації та здійснення профілактики злочинності серед дітей у різних країнах світу. Особливу увагу приділено американському досвіду у сфері ювенальної юстиції та ювенальної превенції. Зокрема, досліджено систему спеціалізованих установ та установ для дітей у США. Проаналізовано міжнародні системні акти щодо ліквідації відповідальності молоді. Проведено аналіз світових моделей ювенальної юстиції, зокрема англосаксонської, континентальної, скандинавської, та вказано на їх особливості. Визначено позитивні риси кожної з цих моделей, які можуть бути запозичені, зокрема, Україною.
Keywords: children’s rights; juvenile delinquency; juvenile justice; juvenile prevention; juvenile responsibility; права дитини; підліткова злочинність; ювенальна юстиція; ювенальна превенція; відповідальність неповнолітніх